Protocol for detection of glial complement expression in relation to amyloid plaques in mouse brain with combined FISH and IHC - Sadhna Rao; Joanna Yung; Melissa Gonzalez Edick; Jesse E. Hanson (STAR Protocols, 2024)
Summary: Complement proteins contribute to neurodegeneration in Alzheimer’s disease (AD) and are secreted by glia surrounding beta-amyloid (Aβ) plaques. We present an optimized protocol for Aβ plaque detection with tyramide-digoxigenin signal amplification. This is combined with a multiplex mRNA fluorescence in situ hybridization (FISH) panel to assay glial-specific complement expression proximal to Aβ plaques in TauPS2APP mice. We describe steps for tissue preparation and mRNA detection. We then detail steps for the detection of Aβ plaques, image acquisition, and analysis. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.